Runoff from Snowmelt - CORPS OF ENGINEERS WASHINGTON DC (1998)
This manual provides technical background and guidance for computing basin snowmelt runoff as is necessary in the design and operation of U.S. Army Corps of Engineers (USACE) water control projects. This manual discusses the basic theoretical principles of snow hydrology and the practical applications of this theory in forecasting and design. It summarizes several important snowmelt runoff models and offers guidelines for model selection. This manual represents an update of EM 1110-2-1406, Runoff from Snowmelt, dated 5 January 1960, which is now obsolete. While many of the basic principles and techniques presented in that manual have been retained, numerous advancements in computer, communications, and data acquisition technologies are now reflected. This manual is applicable to USACE offices in which snow hydrology considerations affect runoff and streamflow derivations.